Improving Web Spam Classification using Rank-time Features - Svore, Krysta M.; Wu, Qiang; Burges, Chris J.C.; Raman, Aaswath (Proceedings of Adversarial Information Retrieval on the Web (AIRWeb), 2007)
In this paper, we study the classification of web spam. Web spam refers to pages that use techniques to mislead search engines into assigning them higher rank, thus increasing their site traffic. Our contributions are two fold. First, we find that the method of dataset construction is crucial for accurate spam classification and we note that this problem occurs generally in learning problems and can be hard to detect. In particular, we find that ensuring no overlapping domains between test and training sets is necessary to accurately test a web spam classifier. In our case, classification performance can differ by as much as 40% in precision when using non-domain-separated data. Second, we show rank-time features can improve the performance of a web spam classifier. Our paper is the first to investigate the use of rank-time features, and in particular query-dependent rank-time features, for web spam detection. We show that the use of rank-time and query-dependent features can lead to an increase in accuracy over a classifier trained using page-based content only.